Patients living with dementia have worse outcomes when undergoing high‐risk procedures. Issue 10 (30th May 2022) - Shah, Samir K.; Adler, Rachel R.; Xiang, Lingwei; Clark, Clancy J.; Cooper, Zara; Finlayson, Emily; Kim, Dae Hyun; Lin, Kueiyu Joshua; Lipsitz, Stuart R.; Weissman, Joel S.
Abstract: Background: Patients with Alzheimer's Disease and Related Dementias (ADRD) undergoing inpatient procedures represent a population at elevated risk for adverse outcomes including postoperative complications, mortality, and discharge to a higher level of care. Outcomes may be particularly poor in patients with ADRD undergoing high‐risk procedures. We sought to determine traditional (e.g., 30‐day mortality) and patient‐centered (e.g., discharge disposition) outcomes in patients with ADRD undergoing high‐risk inpatient procedures. Methods: This retrospective cohort study analyzed electronic health records linked to fee‐for‐service Medicare claims data at a tertiary care academic health system. All patients from a large multi‐hospital health system undergoing high‐risk inpatient procedures from October 1, 2015 to September 30, 2017 with continuous Medicare Parts A and B enrollment in the 12 months prior to and 90 days following the procedure were included. Results: This study included 6779 patients. 536 (7.9%) had ADRD. A multivariable analysis of outcomes demonstrated higher risks for postoperative complications (OR 1.49, 95% CI 1.23–1.81) and 90‐day mortality (OR 1.44 [95% CI 1.09–1.91]) in patients with ADRD compared to those without. Patients with ADRD were more likely to be discharged to a higher level of care (OR 1.70, 95% CI 1.32–2.18) and only 37.3% of patients admitted from home were discharged to home. Conclusions: Compared to those without ADRD, patients living with ADRD undergoing high‐risk procedures have poor traditional and patient‐centered outcomes including increased risks for 90‐day mortality, postoperative complications, longer hospital lengths of stay, and discharge to a higher level of care. These data may be used by patients, their surrogates, and their physicians to help align surgical decision‐making with health care goals.